Number Rinner Games To Improve 5-6 Year-Old Counting Ability - Sinta Sri Rahayu; Imam Tabroni; Jayshree Martin; Wang Fang (Journal of Computer Science Advancements, 2023)
The purpose of this research is to develop educational game tools for improve children's cognitive. The application of APE (Educative Game Tool) was carried out on village children to be exact at Harapan Pertiwi 2 Kindergarten. The researcher used the R&D research method (Research & Development) which aims to determine the application of game tools educative windmill counting in developing the development of cognitive aspects of children. This study used a child subject, namely 4 children between the ages of 4-5 years. Technique data collection using observation, interviews, trials, expert validation, and documentation. Based on the results of the research on the application of the Counting Rabbit Educative Game Tool it is proven feasible to use and able to improve children's cognitive abilities. Children are very enthusiastic in trying the game. The results of the data obtained from the Material Expert found that the total rating score obtained was 63 out of the expected 80, after being converted in the presentation the result was 143.2% in the 'Very Good' category. In the assessment rubric it is known that there is a significant difference in the ability to recognize the concept of numbers in children aged 5-6 years in playing the Counting Rabbit Windmill. In the pre-test activity, an average score of 30 out of 80 was obtained. Meanwhile, in the post-test activity using developed media, an average score of 50 was obtained from the score of 85. The pre-test and post-test activities experienced an increase in the average score of 125.1. So that with the Counting Rabbit Wheel media it can improve children's cognitive abilities.